Application of the FIA score to German rescue helicopter accidents to predict fatalities in Helicopter Emergency Medical Systems (HEMS) crashes - Hinkelbein, Jochen; Schwalbe, Mandy; Neuhaus, Christopher (The journal of emergency medicine, 2012)
Background: In the past several decades, multiple studies have examined factors influencing occupant survival in aviation crashes, but only a few have addressed this question in Helicopter Emergency Medical Systems (HEMS) accidents. The four-point FIA Score is a valid tool to measure fatality risk in aviation crashes. Objective: The aim of the present study was to analyze the performance of the FIA Score when applied to German HEMS accidents, and to determine the prognostic value for fatalities and for survival. Methods: The FIA Score uses three parameters (F=fire; I=Instrument meteorological conditions; A=Away from airport) to determine the fatality risk after crashes. Data for German HEMS accidents between October 1970 and December 2009 were gathered retrospectively from the Federal Agency for Flight Accident Investigation. Accidents were graded according to the FIA Score by two emergency physician-pilots, and crash fatality rates (CFR) were calculated. Results: A total of 99 HEMS accidents were analyzed that occurred from September 1970 to December 2009. In 19.2% of these, at least one occupant was fatally injured. There were 63 accidents (63.6%) that took place with no injuries; 8 occurred with minor injuries (8.1%); and 9 resulted in major injuries (9.1%). A total of 72 data sets were complete and were used for analysis. Depending on the FIA Score (FIA0, FIA1, FIA2, and FIA3), CFRs of 0.0%, 8.1%, 53.3%, and 100.0%, respectively, were calculated. Conclusions: The FIA Score is a valuable tool in German HEMS accident analysis. It can predict fatalities and is easy to use. Thus, it may also be a valuable tool in EMS call centers to predict survival after a crash.